2018
DOI: 10.1002/eap.1695
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of landscape composition on crop yield mediated by specialist herbivores

Abstract: Landscape composition not only affects a variety of arthropod-mediated ecosystem services, but also disservices, such as herbivory by insect pests that may have negative effects on crop yield. Yet, little is known about how different habitats influence the dynamics of multiple herbivore species, and ultimately their collective impact on crop production. Using cabbage as a model system, we examined how landscape composition influenced the incidence of three specialist cruciferous pests (aphids, flea beetles, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 64 publications
(133 reference statements)
4
17
2
Order By: Relevance
“…My result is in line with previous studies that reported a positive impact of woodland overwintering sites on the abundance of rape pollen beetle at multiple scales (Rusch et al, 2013b), and stem weevil (Zaller et al, 2008) and indicates the potential of semi-natural habitats to contribute to ecosystem disservices (i.e. increased pest problems) in some systems (Perez- Alvarez et al, 2018).…”
Section: Direct Effects Of Landscape Complexity and Parasitism On Cersupporting
confidence: 92%
“…My result is in line with previous studies that reported a positive impact of woodland overwintering sites on the abundance of rape pollen beetle at multiple scales (Rusch et al, 2013b), and stem weevil (Zaller et al, 2008) and indicates the potential of semi-natural habitats to contribute to ecosystem disservices (i.e. increased pest problems) in some systems (Perez- Alvarez et al, 2018).…”
Section: Direct Effects Of Landscape Complexity and Parasitism On Cersupporting
confidence: 92%
“…have been shown to alter population dynamics and interfere with prey suppression in agricultural settings (Snyder & Ives, 2001Banks et al, 2008;Rand et al, 2012). Furthermore, landscape complexity in agroecosystems may simultaneously increase natural enemy pressure while bolstering pest populations (Penn, 2018, Perez-Alvarez et al, 2018. Our results suggest that, within the larger ecological context, we can expect differences in aphid suppression stemming from variation in colonization type, keeping all other factorsincluding migration rates and local within-field movement behavior -constant.…”
Section: Discussionmentioning
confidence: 76%
“…Another common strategy for incorporating natural vegetation into agroecosystems, which is more amenable to use in larger-scale agriculture, is to retain weeds, woody plants, and other non-crop vegetation adjacent to or in the margins of crop production areas (Banks 2000, Banks and Stark 2004, Bianchi et al, 2006Gardiner et al, 2009;Fonseca et al, 2017). The adjacent vegetation may act as a source for predators and parasitoids; though increased biological control of crop pests is not always guaranteed (Jonsson et al 2008;Rusch et al, 2013, Bianchi et al, 2017Perez-Alvarez et al, 2018). This highlights the difficulty in establishing a general theory relating non-crop vegetation adjacent to crop fields to pest control.…”
Section: Introductionmentioning
confidence: 99%
“…Studies opposing the cropland to semi-natural habitats failed to define a general rule of thumb regarding the regulation of animal pest epidemics 10,17 . Complex trade-offs between the impact of such landscape elements on both the life cycle of animal pests and their natural enemies have been pointed out 8,18,19 . No clear agreement emerges either for the management of crop pathogens as empirical studies are scarce despite repeated calls for landscape level assessments 11,20. .…”
Section: Articlementioning
confidence: 99%